2006
DOI: 10.1530/eje.1.02124
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with benign thyroid disorders. A review

Abstract: The importance of patient-reported outcomes such as health-related quality of life (HRQL) in clinical research is increasingly acknowledged. In order to yield valid results, the measurement properties of HRQL questionnaires must be thoroughly investigated. One aspect of such a validation process is the demonstration of content validity, i.e. that the questionnaire covers all relevant aspects. We review studies reporting on consequences of thyroid disorders and present the frequency of identified aspects, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
174
2
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(190 citation statements)
references
References 89 publications
9
174
2
5
Order By: Relevance
“…As a result, our findings may not be fully comparable with those of other studies. However, the lack of a questionnaire that assesses the psychological status, as well as the general, clinical and psychosocial aspects of GD in all its complexity, as well as the response to medical and/or surgical treatment, is acknowledged in the international literature [2,18,28]. Surprisingly, our results showed that none of the patient characteristics were significantly associated with a higher HRQOL impairment after surgery.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…As a result, our findings may not be fully comparable with those of other studies. However, the lack of a questionnaire that assesses the psychological status, as well as the general, clinical and psychosocial aspects of GD in all its complexity, as well as the response to medical and/or surgical treatment, is acknowledged in the international literature [2,18,28]. Surprisingly, our results showed that none of the patient characteristics were significantly associated with a higher HRQOL impairment after surgery.…”
Section: Discussioncontrasting
confidence: 58%
“…The incidence of GD is estimated at 5 per 1,000 per year, with a femaleto-male ratio of 7:1 [1]. Patients with untreated GD suffer from a wide range of symptoms, and a substantial portion of them experience limitations in their usual activities, perceive their general health as impaired, and experience social and emotional deterioration [2]. Thus, the impact of GD on the overall well-being of patients cannot be neglected, and some studies have shown that patients with the disease can have a diminished health-related quality of life (HRQOL) [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular system alterations are not uncommon and include decreased output, increased peripheral resistance and reduced blood vo lume, leading to pulse pressure narrowing, increased circulation time, and decreased blood flow to the tis sues, which can be well exemplified by the coolness and pallor of the skin (11). Affective disorders, such as para noid and depressive behavior and impairment of quality of life, may also be found (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Also, psychiatric morbidity, such as psychosis, anxiety disorders and bipolar disease (8), is overrepresented among patients with hyperthyroidism. Hyperthyroid individuals have been reported to have a reduced quality of life (9) and problems with everyday routines, such as housekeeping (10). However, less is known about whether, and if so to which degree, the patients with hyperthyroidism have decreased work ability.…”
Section: Introductionmentioning
confidence: 99%